Wetting and evaporation behavior of dilute sodium dodecyl sulfate droplets on soft substrates under a direct current electric field - Biao Jiang; Shuai Xu; Yingfa Lu; Yingsong Yu (Scientific Reports, 2024)
Abstract Wetting and evaporation behavior of dilute sodium dodecyl sulfate (SDS) droplets on planar polydimethylsiloxane (PDMS) surfaces under a direct current (DC) electric field were experimentally investigated. Two characteristic voltages—actuation voltage and saturation voltage were observed in the electrowetting of dilute SDS droplets on PDMS surfaces. It was found that for dilute SDS droplets with a fixed SDS concentration substrate elasticity has an obvious influence on actuation voltage, and saturation voltage increased with the increase of mass ratio of PDMS surfaces. SDS concentration was also found to obviously influence actuation voltage and saturation voltage when SDS concentration was in a certain range. For the case of evaporation of sessile dilute SDS droplets on PDMS surfaces with the application of a DC electric field, substrate elasticity, SDS concentration and the magnitude of applied voltage were all found to have an influence on the duration of CCR stage. Moreover, contact angle hysteresis for dilute SDS droplets on a planar PDMS 10:1 surface under different applied voltage was measured and it was found that the magnitude of applied voltage greatly influenced contact angle hysteresis, which also depends on SDS concentration and KCl concentration.